Gambaran Kondisi Higiene dan Sanitasi Tempat Pengolahan Pempek pada Industri Rumah Tangga Pangan (IRTP) di Kelurahan 7 Ulu Kota Palembang Tahun 2025 - Amanda Purnanugrah Setya Ningsih; Pitri Noviadi; Maliha Amin; Intan Kumalasari; Hendawati Hendawati (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The Household Food Industry (IRTP) of pempek in 7 Ulu Subdistrict, Palembang City plays an important role in providing traditional food and supporting the local economy, yet hygiene and sanitation conditions remain a concern due to the risk of foodborne diseases. This study aimed to describe the hygiene and sanitation conditions of pempek processing facilities in IRTPs in 2025. A descriptive cross-sectional design was applied involving 52 food handlers from 19 IRTPs selected through total sampling, with data obtained through observation and interviews using checklists and questionnaires. The majority of food handlers were aged 25–42 years (73%), female (94.2%), and had elementary to junior high school education (67.3%), with most having ≤10 years of work experience (86.5%). All equipment hygiene conditions failed to meet the requirements (100%). Food handlers’ hygiene knowledge was mostly moderate (55.8%), while hygiene principles were fulfilled in 84.2% of IRTPs. In terms of sanitation, only 52.6% of buildings met the standards and 42.1% of sanitation facilities were adequate. In conclusion, hygiene and sanitation conditions in pempek IRTPs in 7 Ulu Subdistrict remain varied, with several key indicators unmet, thus requiring continuous supervision, education, and coaching to improve compliance with health standards.